Evaluation of The Internal Control System as Effort as an Effort for Fraud Prevention in Bumdes (Case Study of Midang Village Bumdes) - Baiq Dea Nisrina Atika; Nur Fitriyah; Adhitya Bayu S (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study to determine the effectiveness of the internal control of the BUMDes Maju Berkah as an effort to prevent fraud. The research is descriptive quantitative research method. Population of the research used purposive sampling. This study uses quesionnaires as a primary dara, interviews and documentation as secondary data. The result showed effectiveness of the internal control at BUMDes Maju Berkah reaches level 2, which means BUMDes are in developing level. The meaning is BUMDEs Maju Berkah has implemented internal control but it’s not well documented and it’s implementation is highly dependent on the individual. The implication of research is to evaluate of internal control system ata BUMDes Maju Berkah and it can be seen that internal control plays a role in anticipating or preventing fraud.